THE INFLUENCE OF SELF-EFFICACY AND JOB SATISFACTION ON CAREER DEVELOPMENT THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Rena Jihad; M. Yusuf Qamaruddin; Andi Nadirah; Junaidi, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Organizational citizenship behavior is one of the factors that is related to self-efficacy, career development and job satisfaction. This research aims to determine how much influence self-efficacy, career development and jos satisfaction have on the organizational citizenshop behavior of employees in the East Luwu Regency Regional Government. This research is an explanatory research study with a quantitative approach, the population of this research is employees in the East Luwu Regency Regional Government with a sampling technique using probability sampling. Determining the sample size used the MoE formula so that the research sample size was 100 respondents. Data was collected using a questionnaire where before being distributed to respondents, an instrument test was carried out, namely a validity test and a reliability test. The data that has been collected will be analyzed descriptively and verified using the SmartPLS statistical tool. The research results show that self-efficacy influences organizational citizenship behavior by 0.00, but does not have a significant influence on career development with a value of 0.824. Job satisfaction has a significant effect on organizational citizenship behavior and career development with values of 0.002 and 0.034 respectively. Organizational citizenship behavior influences career development by 0.020. Indirectly, self-efficacy and job satisfaction have a significant positive effect on career development through organizational citizenship behavior as intervening variables with values of 0.049 and 0.050 respectively.